HUBUNGAN SELF DISCLOSURE KEPADA IBU DENGAN LONELINESS PADA EMERGING ADULTHOOD DENGAN STATUS ORANGTUA BERCERAI - Nusya Putri, Fidia; Fauziah Taslim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Parental divorce can affect the quality of family relationships and children’s psychological well-being well into emerging adulthood, in part through the emergence of feelings of loneliness. One factor that plays a role in reducing loneliness is self-disclosure to one’s mother. This study aims to examine the relationship between self-disclosure to one’s mother and loneliness in emerging adults whose parents are divorced. This study employs a quantitative approach using a correlational method to examine the relationship between variables. The subjects of this study are individuals in emerging adulthood with divorced parents. The sample was selected using purposive sampling and snowball sampling techniques. Meanwhile, data were collected using a self-disclosure to mother scale and a loneliness scale. The data were then analyzed using Spearman’s rank correlation. The results indicate a significant negative relationship between self-disclosure to one’s mother and loneliness among emerging adults with divorced parents (r = -0.441; p < 0.001). These findings indicate that the higher the level of self-disclosure to one’s mother, the lower the level of loneliness experienced by the individual. Conversely, the lower the level of self-disclosure to one’s mother, the higher the level of loneliness felt. Furthermore, the level of self-disclosure in this study falls into the high category, while loneliness falls into the moderate category. These findings highlight the importance of self-disclosure to one’s mother as a factor that can help reduce feelings of loneliness among emerging adults who have experienced parental divorce.